2018
DOI: 10.1097/mol.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Towards more specific treatment for diabetic dyslipidemia

Abstract: Purpose of review Treatment of diabetic dyslipidemia is necessary because of its impact on cardiovascular disease, which is the leading cause of death in patients with diabetes. In the past, standard treatment of diabetic dyslipidemia focused only on correcting lipids. Although this remains the mainstay of treatment, because new antihyperglycemic treatments reduce cardiovascular events with minimal effect on dyslipidemia, a new approach is both timely and relevant. Recent findings LDL-lowering remains the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Most cases of T2D are accompanied by dyslipidemia, which is an important cause of T2D incidence and development and is also a treatable relevant aspect for subsequent cardiovascular complications that may develop in patients with T2D [33,34,35]. The liver is an important metabolic organ in the human body and directly affects the metabolism of glucose and lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Most cases of T2D are accompanied by dyslipidemia, which is an important cause of T2D incidence and development and is also a treatable relevant aspect for subsequent cardiovascular complications that may develop in patients with T2D [33,34,35]. The liver is an important metabolic organ in the human body and directly affects the metabolism of glucose and lipids.…”
Section: Resultsmentioning
confidence: 99%
“…CETP-mediated TG enrichment and increased lipolysis of LDL by hepatic lipase increase the number of atherogenic small dense LDL particles (9,10). The total burden of atherogenic particles and remnants are contributors to elevated non-HDL cholesterol level and Apo B measured in type 2 diabetes (11).…”
Section: Introductionmentioning
confidence: 99%
“…The ACCORD-lipid trial suggested that addition of fenofibrate therapy may reduce CVD events in diabetic patients with hypertriglyceridemia and low HDL-C [28][29][30]. Evidence from multiple studies have evaluated the potential effect of PCSK9 inhibitors, bile acid sequestrants, niacin, omega-3-fatty acids as add-on therapies to statins for patients with diabetes [29,30]. However, the incremental benefit of these drugs in patients with diabetes and comorbid ASCVD needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%